Determination of Anti-melanogenic Activity of Phlomis kurdica in Human Melanoma SKMEL-3 Cells: Anti-melanogenic activity of Phlomis kurdica in human melanoma SKMEL-3 cells - Mona Salimi; Raheleh Tahmasvand; Parisa Sarkhai; Maryam Baeeri (Iranian Journal of Pharmaceutical Sciences, 2016)
The present study was designed to investigate the anti-melanogenic and cytotoxic activities of methanol extract of Phlomis kurdica. The antioxidant and anti-tyrosinase activity of MeOH extract from P. kurdica (MPk) were examined by DPPH radical scavenging and mushroom tyrosinase activity assays (in vitro), respectively. Furthermore, the effect of MPk on the melanin content, cellular tyrosinase activity and cytotoxicity was studied on human melanoma SKMEL-3 cells (in vivo). The results showed that the MPk inhibited DPPH radicals and mushroom tyrosinase activity in a dose dependent-manner, but these effects were weaker than positive controls. The extract revealed cytotoxic effect in SKMEL-3 cells at high concentrations (> 0.2 mg/mL). Moreover, at concentration of 0.25 mg/mL, it reduced melanin content and cellular tyrosinase activity about 7% and 28% of control, respectively. These findings suggest that the MPk can be considered as a cytotoxic extract in melanoma skin cancers and exhibited inhibitory effect on melanogenesis process.